The ersatz elevator - Snicket, Lemony; Helquist, Brett (New York : HarperCollins Publishers, 2001)
The woeful saga of the Baudelaire orphans continues as evil Count Olaf discovers their whereabouts at Esmé Squalor's seventy-one bedroom penthouse and concocts a new plan for stealing their family fortune.
z
b
b
Keywords: Orphans -- Fiction; Siblings -- Fiction; Humorous stories